2012
DOI: 10.4236/ijcm.2012.37114
|View full text |Cite
|
Sign up to set email alerts
|

Wrongly Prescribed Half Tablets in a Swiss University Hospital

Abstract: <p class="MsoNormal"> <b><span lang="EN-GB">Background:</span></b><span lang="EN-GB"> Prescription of </span><span lang="EN-GB">1/2</span><span lang="EN-GB"> tablets is a widespread practice, mainly to achieve dose flexibility and to facilitate swallowing. However, tablet splitting includes several disadvantages, like destruction of galenic formulation, stability problems, and unequal amount of active ingredient that may reduce effectiveness or result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Splitting was inappropriate for 2.7% of all drugs, mainly because of the absence of a score line. A retrospective study performed at the University Hospital Basel in Switzerland showed similar results [ 11 ]. Of the 36,751 electronic prescriptions delivered in 2011 at discharge, 3,724 (10.1%) contained the mention “1/2” and concerned 4,888 single tablets.…”
Section: Introductionmentioning
confidence: 61%
“…Splitting was inappropriate for 2.7% of all drugs, mainly because of the absence of a score line. A retrospective study performed at the University Hospital Basel in Switzerland showed similar results [ 11 ]. Of the 36,751 electronic prescriptions delivered in 2011 at discharge, 3,724 (10.1%) contained the mention “1/2” and concerned 4,888 single tablets.…”
Section: Introductionmentioning
confidence: 61%
“…In the few studies on the frequency of tablet splitting in hospitals, Arnet et al and Quinzler et al have observed higher splitting frequency (10.1% and 8.5%, respectively) than the one observed in the study reported here (4.5%). 9,22 The differences may stem from the varying characteristics of the hospitals, including the number of beds, medical specialties available, and patient profile. Regardless of the inter-hospital variation, the prevalence of tablet splitting is clearly high, which underscores the need to understand its causes and propose alternatives to mitigate its potential adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is far higher than in other studies because our study involved children aged one to 7 years whereas other studies have involved a mixed group of patients. [ 18 19 20 ] Despite it being well-known that coated, unscored, and special formulations such as sustained-release and controlled-release, should not be split,[ 21 22 ] patients are prescribed such formulations and advised to split them as they are the only formulations available for prescribing in our hospital. VPA was the most commonly prescribed drug as well as in split forms followed by PHY.…”
Section: Discussionmentioning
confidence: 99%